EDUKASI MEDIA PEMBELAJARAN BERBASIS APLIKASI DI SMK NEGERI 48 JAKARTA - Muhammad Alfadh Jiyad; Reisha Febriliana Hapsari; Putri Utami Ramadhan; Nur Amalia; Hermina Manihuruk; Sunardin Sunardin; Andreas Bramantyo (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The lack of visual and interactive learning resources in the Visual Communication Design (DKV) program presents challenges for students at SMK Negeri 48 Jakarta in understanding Digital Marketing material. This program aimed to enhance students' understanding and engagement through an interactive learning application on the "Content Creator" theme. Conducted at SMK Negeri 48 Jakarta, this program involved 11th-grade DKV students as partners. The Activities carried out are educational which includes planning, developing content and visual assets, application testing, and evaluation. Results indicated a significant improvement in students' comprehension, as shown by a 71.86% increase in the average post-test scores compared to the pre-test. The application demonstrated a positive impact on students' interest in technology-based learning tailored to visual needs. This innovation is particularly valuable for DKV students as it integrates visual elements, animations, and educational games. This program can serve as a model for similar initiatives in other schools, adapted to various fields of study. It underscores the importance of integrating technology as a modern learning resource in the digital era